(untitled) (Plant Tissue Culture and Biotechnology, 2019)
Multiple shoots were obtained from both shoot tips and nodal segments cultured on MS fortified with different concentrations of BAP and Kn singly or in combination with low concentration of NAA. Maximum number of shoots (9.28 ± 0.61) were found on MS supplemented with 1.5 mg/l BAP and 05 mg/l NAA. In vitro regenerated shoots were separated and transferred onto half and full-strength MS supplemented with different concentration of IBA, IAA and NAA for root induction. Full strength MS containing 0.2 mg/l IBA was found to be best for root induction where 93.33% shoots were rooted. In vitro regenerated plants grew normally without showing any morphological variation and flowered after 40 days of transplantation.